Peripheral Nervous System Pathways - Frank Reilly; Edwin Allen (Association of American Medical Colleges, 2010)
Abstract This resource is a web-based tutorial aimed at conveying information about the neurons forming the peripheral nervous system and the nomenclature (functional components) used to classify them. The objective was to stimulate self-directed learning by creating animated diagrams summarizing cranial and spinal nerve pathways accompanied by detailed text summarizing deficits and tests of functional integrity. The courseware is user friendly and achieves a dimension that cannot be attained by using conventional textbooks. It complements didactic and practical (dissection) activities of beginner health care professionals enrolled in human structure courses. Since implementation of this resource in 2001, students have scored 8% more correct answers on written exam questions. Learner surveys have rated this material the highest among the resources provided for the human structure courses.